2021
DOI: 10.1002/rmv.2285
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of public health measures to prevent the transmission of SARS‐CoV‐2 at mass gatherings: A rapid review

Abstract: Mass gatherings play an important role in society, but since the onset of the Covid-19 pandemic, they have generally been restricted in order to mitigate transmission of SARS-CoV-2. The aim of this study was to summarise the evidence regarding the effectiveness of public health measures at preventing the transmission of SARS-CoV-2 at mass gatherings, and hence inform guidance on the organisation of these events. A rapid review was undertaken in Cochrane, Embase (OVID), Medline (OVID), Google, Web of Science an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 29 publications
(211 reference statements)
0
23
0
Order By: Relevance
“…Third, through the implementation of combinations of layered control measures—including widespread testing, contact tracing, and isolating; proper use of face masks; physical distancing; limitations on mass gatherings; and improved ventilation systems at workplaces— R decreases to less than 1, so the epidemic declines. 16 , 26 Early implementation of public health and social measures—including closing businesses and venues, banning public events, launching public information campaigns, and requiring the use of face masks—is more effective at keeping cumulative cases and deaths low than implementation at a later stage. 27 We call this a suppression strategy.…”
Section: Section 1: Conceptual Framework For Understanding Pandemicsmentioning
confidence: 99%
“…Third, through the implementation of combinations of layered control measures—including widespread testing, contact tracing, and isolating; proper use of face masks; physical distancing; limitations on mass gatherings; and improved ventilation systems at workplaces— R decreases to less than 1, so the epidemic declines. 16 , 26 Early implementation of public health and social measures—including closing businesses and venues, banning public events, launching public information campaigns, and requiring the use of face masks—is more effective at keeping cumulative cases and deaths low than implementation at a later stage. 27 We call this a suppression strategy.…”
Section: Section 1: Conceptual Framework For Understanding Pandemicsmentioning
confidence: 99%
“…In relation to the use of RADTs for pre‐event screening or serial testing, the additional benefit of RADTs over and above that of other public health measures is still unclear, especially if the prevalence of SARS‐CoV‐2 is low. A recent review found that implementing a package of public health measures, which could include RADTs, may reduce the risk of SARS‐CoV‐2 transmission at mass gatherings; however, it was not possible to determine the impact of any single measure 51 . The requirement for trained professionals to obtain or supervise samples and administer RADTs at events, presents additional logistical and cost implications, but is arguably necessary to ensure that testing is rigorous, of high quality, and prevents gaming of the system (e.g., by using someone else's test result or conducting minimal inadequate swabbing).…”
Section: Discussionmentioning
confidence: 99%
“…Public services are the most visible measure of government performance. Given that the main function of the government is to serve the community, the government needs to continue to improve the quality of service [1]. The public can directly assess the government's performance based on the quality of public services received, because the quality of public services is in the interest of many people and the impact is directly felt by people from all walks of life, where success in building public service performance in a professional, effective, efficient and accountable manner will raise the positive image of the government.…”
Section: Intoductionmentioning
confidence: 99%